The clinical application of transcranial direct current stimulation in patients with cerebellar ataxia: a systematic review. (3rd July 2021) - Orrù, Graziella; Cesari, Valentina; Conversano, Ciro; Gemignani, Angelo
Abstract: Aim: The aim of this review was to investigate the effects of transcranial direct current stimulation (tDCS) on motor function in patients with cerebellar ataxia. Materials and methods: Our systematic review has been performed by searching full-text articles on Pubmed and Scopus. Only studies investigating the motor effects of tDCS in patients with cerebellar ataxias were considered. A qualitative analysis of data was performed, as the methodology of the selected studies was highly heterogeneous. Results: Our search yielded a total of twenty-seven hits. Based on the inclusion criteria, 19 of these were excluded and 89 were retained (number of patients = 81).The results reviewed so far suggest that tDCS over cerebellum combined or not with extra-cerebellar areas might be promising approach to improve motor outcomes, with a greater success in patients less impaired. In particular, it is been shown an improvement in both clinical measures assessing cerebellar deficits (i.e. gait, stance and oculomotor disorders) and performance measures (finger dexterity, upper limb coordination and gait speed). Some of the assessed investigations highlighted a restore effect of cerebellar brain inhibition pathway and resting motor threshold after tDCS. Conclusions: tDCS could be considered an effective approach to promote plasticity in patient with cerebellar ataxia with significant motor effects. Future studies, with larger sample sizes are needed in order to evaluate the effective tDCS benefits on motor functionality. Due to the limited number of studies available so far, conclusions on the effectiveness of the reported approaches are premature.